Pengaruh Karakteristik Pekerjaan, Kepemimpinan dan Iklim Sekolah terhadap Kepuasan Kerja Guru - Delvi Andriadi; Indra Prasetia; Amini Amini (Journal Of Administration and Educational Management (ALIGNMENT), 2022)
Job satisfaction is influenced by many factors, including job characteristics, school climate, and leadership. The purpose of this study was to determine the effect of job characteristics, leadership and school climate on job satisfaction of JSIT High School teachers in Medan City. The research population is teachers from SMA IT AL-Fityan, SMA Al-Amjad, and SMA Nurul Azmi, all totaling 122 people. The research sample was selected randomly or randomly. The number of samples was determined by the Slovin formula at a 95% confidence level, so that there were 94 teachers consisting of 29 male teachers and 65 female teachers. The instrument used is a questionnaire. Furthermore, reliability and validity tests were carried out. The data were analyzed using coefficient, correlation and regression analysis techniques. The results of the coefficient calculation show that there is a significant relationship, (1) the variable of the teacher's work characteristics X1Y = 3,300, (2) the variable of the principal's leadership X2Y = 2,92, (3) the variable of the school climate X3Y = 5,537 and (4) the work characteristics of the teacher, Principal leadership and school climate X1X2X3Y = 3.892 at the 5% confidence level. Looking at the strength of the relationship using the Spearman rank test, it was found that (1) the variable of teacher work characteristics X1Y = 0,542** is interpreted as having a strong and direct correlation, (2) the principal leadership variable X2Y = 0.678** is interpreted as a strong and direct correlation, (3) the variable school climate X3Y = 0.806** means a very strong and unidirectional correlation. The results of the regression calculation show that the contribution of teacher work characteristics to satisfaction is 38%, for principals' leadership 22.6% and for school climate 42.8%. The suggestion is that it is necessary to develop other variables that contribute to teacher job satisfaction. Keywords: Characteristics of teacher work, principal leadership, school climate and teacher satisfaction.